Peningkatan Pelayanan Administrasi Masyarakat di Desa Loa Duri Ulu Menggunakan Sistem Informasi Berbasis Web (SIMPELDES) - Faldi Faldi; Naufal Azmi Verdikha; Intan Kinanthi Damarin Tyas (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Administrative control is a way for an institution to archive or discipline its administration correctly. Loa Duri Ulu Village is one of the villages located in Loa Janan District, Kutai Kartanegara Regency, East Kalimantan. Currently, the service administration system in the village of Loa Duri Ulu is still manual. Every community that needs documents related to a population still has to come to the village office to take care of these documents and record them into a book manually to impact the village office in carrying out their duties. This community service aims to overcome administrative service problems in Loa Duri Ulu Village by creating an administrative service information system. In this research-based community service, an iterative model strategy is used in the Software Development Life Cycle (SDLC), including several stages. This method consists of 5 stages: Planning Stages, Analysis Stages, Web Design Stages, SIMPELDES web Implementation Stages, and Maintenance Stages. The result of this service is that a web called the SIMPELDES web has been created and designed where this web has service features for various types of inputting and archiving letters in Loa Duri village. With an administrative application system and community service that is connected to the community database, it will be faster to get the required letters, both new letters, and old ones.